When the relatively poor prosper: the Underdog Effect on charitable donations - Bradley, Alex; Lawrence, Claire; Ferguson, Eamonn (SAGE, 2018)
In fundraising, it is common for the donor to see how much a charity has received so far. What is the impact of this information on a) how much people choose to donate and b) which charity they choose to donate to? Conditional cooperation suggests that people will donate to the charity that has received the most prior support, while the Underdog Effect suggests increased donations to the charity with the least support. Across 2 laboratory experiments, an online study (combined N = 494) and a qualitative survey (N = 60), a consistent preference to donate to the charity with the least prior support was observed. Thus, the Underdog Effect was supported. We suggest people will show a preference for the underdog if there are two or more charities to donate to, one of the charities is at a disadvantage and people have little pre-existing loyalty to either charity.